2018
DOI: 10.1542/peds.2017-3651
|View full text |Cite
|
Sign up to set email alerts
|

The Grief of Mothers After the Sudden Unexpected Death of Their Infants

Abstract: BACKGROUND:The loss of a child is associated with elevated grief severity, and sudden infant death syndrome (SIDS) is the leading cause of postneonatal mortality in the United States. The diagnosis of prolonged grief disorder (PGD) has gained broader acceptance and use. Little is known about PGD in mothers after SIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…On the level of those affected, bereaved parents associate blame and judgment with the use of different terms [27], with ASSB and undetermined cause of death carrying a stigma of implied blame, even when evidence does not support that parents have caused harm. Parents suffer from severe grief-related symptoms [28], and few options are available to obtain enhanced diagnostics for better explanations, despite recent advances in undiagnosed diseases [29].…”
Section: The Problemmentioning
confidence: 99%
“…On the level of those affected, bereaved parents associate blame and judgment with the use of different terms [27], with ASSB and undetermined cause of death carrying a stigma of implied blame, even when evidence does not support that parents have caused harm. Parents suffer from severe grief-related symptoms [28], and few options are available to obtain enhanced diagnostics for better explanations, despite recent advances in undiagnosed diseases [29].…”
Section: The Problemmentioning
confidence: 99%
“…The seriousness of such losses is also reflected in several studies that have shown increased mortality over many years among parents who lose children, especially among mothers (Espinosa & Evans, 2013;Harper, O'Connor, & O'Carroll, 2011;Li, Precht, Mortensen, & Olsen, 2003;Rostila, Saarela, & Kawachi, 2011). A very high incidence of psychological difficulties (K. Dyregrov, Nordanger, & Dyregrov, 2003;Murphy, Johnson, & Lohan, 2002), prolonged grief disorder (PGD) (Goldstein et al, 2018) and functional impairment (Wilcox, Mittendorfer-Rutz, Kjeldgård, Alexanderson, & Runeson, 2015) has been found years after the death of a child.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to its population, South Asia has the highest number of studies per slum inhabitant (Table 3). Most of the studies were conducted in India (109) and Bangladesh (30). In contrast to the high number of studies for the slums of Nairobi, the medical studies for India are spread across the whole country (cf.…”
Section: Fstmentioning
confidence: 99%
“…Looking at the cross-national scale, only eight studies are available. There is one cross-national study on communicable diseases [84] in Burkina Faso and Kenya, one on malnutrition between Chile and Kenya [106], one on nurturing care in Angola and Kenya [107], one on contraceptive methods in Bangladesh and Kenya [108], one on early child loss in South Africa and India [109], and three non-specific on noise annoyance and sensitivity [110] between dwellers of informal settlements in South Africa and inhabitants of Switzerland, one on community health in three Melanesian countries [111], and one on urban growth and water access in sub-Saharan Africa [112].…”
Section: Analysis By Scalementioning
confidence: 99%